THE CONSUMER INTEREST IN YOUTH CASUAL FASHION DESIGN CREATIONS WITH THE APPLICATION OF FOOTBALL MOTIFS - Aliya Nurhalimah; Adinda Putri; Sugiyem, Sugiyem (Universitas Pendidikan Ganesha, 2025)
This research aims to create a collection of casual fashion designs for teenagers using motifs inspired by football elements. This research method is qualitative research with a Research and Development approach. This research was conducted by conducting a literature study, designing four casual fashion designs for teenagers, and then conducting an online survey of respondents aged 15-25 years to find out their interest in and liking of fashion design. The results of the preference test showed that the four designs were positively received by most respondents, both in terms of design suitability with the source of the idea, fashion form, color, accent/detail, texture, material, and product price. The most in-demand design is the third design, with a percentage of enthusiasts of 51.9%.